Electronic Health Record–Assisted Reflex Urine Culture Testing Improves Emergency Department Diagnostic Efficiency. (May 2020) - Coughlin, Ryan F.; Peaper, David; Rothenberg, Craig; Golden, Marjorie; Landry, Marie-Louise; Cotton, Jeffrey; Parwani, Vivek; Shapiro, Marc; Ulrich, Andrew; Venkatesh, Arjun K.
The authors evaluated the effectiveness of an electronic health record (EHR)-based reflex urine culture testing algorithm on urine test utilization and diagnostic yield in the emergency department (ED). The study implemented a reflex urine culture order with EHR decision support. The primary outcome was the number of urine culture orders per 100 ED visits. The secondary outcome was the diagnostic yield of urine cultures. After the intervention, the mean number of urine cultures ordered was 5.95 fewer per 100 ED visits (9.3 vs 15.2), and there was a decrease in normal, or negative, cultures by 2.42 per 100 ED visits. There also was a statistically significant decrease in urine culture utilization and an increase in the positive proportion of cultures. Simple EHR clinical decision-support tools along with reflex urine culture testing can significantly reduce the number of urine cultures performed while improving diagnostic yield in the ED.